Crime and terror of social exclusion: the case of 13 imams in Bulgaria - Panayotov, Bogdan (European journal of criminology, 2019)
According to conventional wisdom, radicalization is explained through the presence in a city of, for example, organized crime, melting pots, illegal drugs and arms trafficking. However, the Bulgarian case (and specifically the precedent of 2014) challenges this logic because it shows a correlation between social marginalization and radicalization. This article explores this link and determines that the causes of radicalization include the lack of an adequate state presence in areas inhabited by certain marginalized minority groups in Bulgaria and the latter’s choice to adopt radical views to gain money and merely to make both ends meet.